Technical efficiency and reduction in input costs in agriculture: case of genetically modified cotton - Niti Mehta (Agricultural Economics Research Review, 2023)
Adoption of labour-saving agricultural technologies is often determined by peak-season labour scarcity and uncertainty in labour supply, besides the need to reduce overall cost of production. Adoption of labour-saving technological innovations could also be justified on efficiency grounds. Technology-led agricultural growth is believed to ensure economic gains to cultivators, increase in real wages and creation of employment opportunities. This paper estimates changes in mean technical efficiency in herbicidetolerant cotton, vis-à-vis conventional Bt cotton crops. Analysis indicates that use of herbicide-tolerant technology is technically more efficient, as it reduces wastage of purchased farm inputs due to absence of crop-weed competition, in addition to ease of cultivation related operations termed in literature as nonpecuniary benefits.